Macrophage caspase-8 inhibition accelerates necrotic core expansion in atheroma plaque in mice - Pilot, Thomas; Solier, Stéphanie; Jalil, Antoine; Magnani, Charlène; Vanden Berghe, Tom; Vandenabeele, Peter; Masson, David; Solary, Eric; Thomas, Charles (Frontiers in Immunology, 2025)
Background and aimsCell death plays a central role in atheroma plaque progression and aggravation. This study investigates the role of caspase-8 in regulating macrophage cell death modalities, specifically apoptosis and necroptosis, within atheroma plaques.MethodsBone marrow from caspase-8-deficient (Casp8komac) and cohoused wildtype littermates were transplanted in atherosclerosis-prone Ldlr-/- recipient mice fed with a proatherogenic diet. Aortic plaque development, necrotic core formation, and cell death were analyzed through histological and biochemical assays. In vitro investigation of macrophages exposed to atherogenic stimuli assessed the effects of caspase-8 inhibition on apoptotic and necroptotic pathways.ResultsDespite lower plasma cholesterol levels and reduced number of inflammatory monocytes, caspase-8-deficient mice exhibited more pronounced atherosclerotic lesions with enlarged necrotic cores and an increased number of dead cells. In vitro, in macrophages exposed to oxidized LDL or oxysterols, the inhibition of caspase-8 revealed a shift from apoptosis to necroptosis as confirmed by increased phosphorylation of MLKL along with decreased cleavage of caspase-3 and -7.Discussion and perspectivesThe study highlights the role of caspase-8 in atherosclerosis in tuning the balance between apoptosis and necroptosis. Caspase-8 inhibition leads to a switch towards necroptosis and accumulation of dead cell corpses that contributes to enhanced plaque severity. These findings suggest that reducing caspase-8-regulated necroptosis and necrosis in macrophages could represent a therapeutic strategy to stabilize plaques and reduce cardiovascular risk.